THE INFLUENCE OF QUANTITATIVE RESEARCH IN BUSINESS & INFORMATION TECHNOLOGY: AN APPROPRIATE RESEARCH METHODOLOGY PHILOSOPHICAL REFLECTION (American Journal of Interdisciplinary Research and Development, 2022)
The purpose of this study is to examine quantitative methodology in the context of Business & Information Technology research. The study provides an overview of the evolution of methods, paradigms, and interpretive frameworks in Business & Information Technology, explores important benefits, and limits, and examines fresh trend quantitative data in a single research project to reconcile methods for Business & Information Technology. The appropriate selection of a research technique is a critical decision for effective scientific research, and it is mostly dependent on matching research objectives to the features of accessible research procedures. One of the most difficult decisions a researcher must make is which research method to use. This is because researchers in the fields of economics, business, and technology must choose from a lot of different approaches and techniques. As a result, the purpose of this study is to examine an appropriate research technique for identifying and assessing essential strategic management aspects and phases, as well as difficulties linked to (a) quantitative research and (b) strategy (c) management (d) information systems, (e) digital systems. According to the findings, research methods, in addition to quantitative research, provide an engaging style of conducting business research.